Development of Low‐vacuum SIMS instruments with large cluster Ion beam. (15th September 2016) - Suzuki, K.; Kusakari, M.; Fujii, M.; Seki, T.; Aoki, T.; Matsuo, J.
Abstract : Large cluster ions such as Arn + (n > 1000) are expected to have a better transmission factor than monomer ions or other small cluster ions because of their large mass, and thus they might be used as a probe in secondary ion mass spectrometry measurements even at low vacuum pressure. In this study, we examined the transmission and sputtering properties of Ar gas cluster ion beam under low vacuum. Current images of a Ni mesh (400 line/inch) obtained with varying target chamber pressure under low vacuum (<50 Pa) indicated that cluster ions could reach the target without wide divergence. Furthermore, it was demonstrated that cluster ions could sputter organic samples even at 80 Pa. Although the sputtering efficiency decreased by two orders of magnitude at 80 Pa, beam focusing (~20 µm) was achieved with a beam current of 4 nA, that is, one or two orders of magnitude higher than the conventional Ar gas cluster ion beam source. From these results, we concluded that low‐vacuum secondary ion mass spectrometry measurements (<80 Pa) might be achievable. Copyright © 2016 John Wiley & Sons, Ltd.